2012
DOI: 10.5120/ijais12-450676
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Biometric Authentication System for Efficient and Reliable e-Payment System in Nigeria

Abstract: The recently introduced cashless economy with the cash-lite banking by the Central Bank of Nigeria (CBN) has engineered most Nigeria banks to introduce e-payment and e-transact solutions to support the policy. However, one of the major problems limiting the growth of this new move in Nigeria is the absence of secure and reliable e-payment systems. The problems associated with the implementation of a secure e-payment systems in the country stem from card thefts, internet fraud and identity theft e.t.c, which ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…There is another technique represented by Aranuwa and Ogunniye [13]. They purposed solution to Enhanced Biometric Authentication System in Nigeria for Efficient and Reliable e-Payment.…”
Section: Figure 3: Device Monitoringmentioning
confidence: 99%
“…There is another technique represented by Aranuwa and Ogunniye [13]. They purposed solution to Enhanced Biometric Authentication System in Nigeria for Efficient and Reliable e-Payment.…”
Section: Figure 3: Device Monitoringmentioning
confidence: 99%
“…However, with recent development, experiences show that the conventional method of identification is not all that reliable with the recent fraud cases. Hence, an embedded biometric authentication scheme for Automated Teller Machine (ATM) as presented by [18] is recommended. This provides a better means to secure our electronic transactions better than conventional methods.…”
Section: Atm Securitymentioning
confidence: 99%
“…The system reduced environmental pollution problem cause by excess number of plastic cards. It also saves time, cost, and efforts compared with card-based ATMs and also saves Aranuwa and Ogunniye (2012) developed an effective biometric system for authentication of epayment platform that consolidated security as well as fraud prevention in Nigeria. The archetype of the developed system with multi-stage recognition mechanism designed in the study indicated and demonstrated that the enhanced method would aid the elimination of insecurity in online payments with a realistic degree of trust and acceptability for wider patronage of electronic payment solutions in Nigeria.…”
Section: Related Workmentioning
confidence: 99%